A Porous Cadmium(II) Framework: Synthesis, Crystal Structure, Gas Adsorption, and Fluorescence Sensing Properties. Issue 10 (7th April 2017) - Zhou, Pingping
Abstract : The Cd II compound, namely [Cd(Tppa)(SO4 )(H2 O)] n (1 ) [Tppa = tris(4‐(pyridyl)phenyl) amine], was synthesized by the reaction of CdSO4 · 8H2 O and Tppa under solvothermal conditions. Single crystal X‐ray diffraction analysis revealed that compound1 features a 3D porous framework based on 1D inorganic –[Cd–SO4 –Cd] n – chains. Topological analysis reveals that compound1 represents a trinodal (3, 4, 6)‐connected topological network with the point symbol of {6.7 2 }2 {6 4 .7.10}{6 4 .7 5 .8 4 .10 2 }. Gas adsorption properties investigations indicate that compound1 exhibits moderate adsorption capacities for light hydrocarbons at room temperature. Luminescencence property studies revealed that this Cd II compound exhibits high fluorescence sensitivity for sensing of CS2 molecule. Abstract :